EFEK JUMLAH PADAT TEBAR TERHADAP TINGKAT KELANGSUNGAN HIDUP BENIH IKAN BAWAL AIR TAWAR (Colossoma macropomum) UKURAN 2-3 CM DI BAK-BAK PERCOBAAN - Muhajir Muhajir; Fikri Islamudin (Universitas Mataram, 2026)
Freshwater bawal (Colossoma macropomum) is a high-value fishery commodity, widely consumed due to its rapid growth and meat quality. However, bawal seeds sized 2-3 cm face high mortality rates, often influenced by stocking density. This study aims to determine the optimal stocking density to maximize the survival rate of these seeds. The research was conducted over 14 days (January 10–24, 2026) using an experimental method with a Completely Randomized Design (CRD), consisting of five treatments and five replications. The treatments involved different stocking densities: A (5 fish/L), B (15 fish/L), C (25 fish/L), D (35 fish/L), and E (45 fish/L). The specimens were fed commercial pellets three times daily. Data were analyzed using one-way ANOVA followed by an HSD (Honestly Significant Difference) test at a 5% significance level. The results indicate that stocking density significantly affects the survival rate. Treatment A (5 fish/L) yielded the highest survival rate at 98.0%. Water quality remained stable throughout the study, with temperatures at 27.5–27.9°C, dissolved oxygen at 3.8–4.0 ppm, and pH at 7.5–7.8.